From small country churches to explosion into megachurches: A modern Pentecostal cultural fit for the Assemblies of God in South Africa - Kelebogile T. Resane (Verbum et Ecclesia, 2022)
This article examines the evolutionary journey of Assemblies of God in South Africa from small country churches into explosion of megachurches. This Pentecostal denomination is categorised as a classical Pentecostal church that evolved as a missionary church from the early twentieth century. It was officially registered in South Africa in 1917. Historically, it developed as small fellowships in small structures; however today, it has exploded into a huge denomination spread in some geographical locations as local megachurches. Through literature reviews, the objectives are to reveal the rationale behind this explosion, which are the church organisation, emphasis on education, entrepreneurship spirit, apostolic heritage and local church autonomy based on the group system. Results of this explosion are accounted to vigorous evangelism, and Bible-oriented religion such as kerygma, diakonia, koinonia and rhetorics to be culturally and contextually relevant. Assemblies of God embrace African gregarious worldviews and apostolic practices of ecclesial life. This apostolic outlook invokes the discussions on leadership principles. It also influences the church polity exercised by many African megachurches. Shifts from orthodox Pentecostal doctrines such as glossolalia, divine healing and eschatological expectations are examined. The conclusion is while the neo-Pentecostal movement replaces these doctrines by prosperity gospel, personal prophecies and motivational rhetorics instead of sound biblical hermeneutics, Assemblies of God in South Africa remain rooted in their evangelical and classical Pentecostal tradition.